Anionic Access to Silylated and Germylated Binuclear Heterocycles. Issue 32 (3rd July 2014) - Boddaert, Thomas; François, Cyril; Mistico, Laetitia; Querolle, Olivier; Meerpoel, Lieven; Angibaud, Patrick; Durandetti, Muriel; Maddaluno, Jacques
Abstract A simple access to silylated and germylated binuclear heterocycles, based on an original anionic rearrangement, is described. A set of electron‐rich and electron‐poor silylated aromatic and heteroaromatic substrates were tested to understand the mechanism and the factors controlling this rearrangement, in particular its regioselectivity. This parameter was shown to follow the rules proposed before from a few examples. Then, the effect of the substituents borne by the silicon itself, in particular the selectivity of the ligand transfer, was studied. Additionally, this chemistry was extended to germylated substrates. A hypervalent germanium species, comparable to the putative intermediate proposed with silicon, seems to be involved. However, a pathway implicating the elimination of LiCH2Cl was observed for the first time with this element, leading to unexpected products of the benzo‐oxa (or benzo‐aza) germol‐type.